Effect of Temperature and Stirring Speed in Obtaining the Osmotic Dehydration of Jinger (Zingiber Officinale) - Cañazaca Tito, Nancy (2022)
The objective of this research was to evaluate the effect of temperature and agitation speed on weight loss (WeL%), water loss (WaL%) and solids gain (SG%) in the osmotic dehydration of ginger cubes. (Zingiber officinale). The applied parameters were: osmotic solution temperature 26, 36, and 46°C, stirring speed of 30, 50 and 80 rpm, sample/osmotic solution ratio of 1:16 (p/p), sucrose concentration at 60% and experiment time 0, 15, 30, 45, 60, 75, 90, 105 and 120 min. The results showed that the temperature was the parameter that most influenced the WaL%, WeL%, and SG%, compared to the agitation speed it had a lower influence on the WaL%, WeL%, and SG%, this indicates that the high temperatures cause changes in the permeability of the cell membrane of the food, which generates greater transfer. The 26°C and 30 rpm treatment showed a higher diffusivity (De) with 5,20 x 10-4. The 46°C and 30 rpm treatment reported higher moisture losses with 35%, the 26°C and 30 rpm treatment presented an increased pH variation from 6.62 to 5.27, the 36°C and 50 rpm treatment showed a constant acidity of 0.05% and the treatment of 46°C and 80 rpm increase variation in soluble solids concentration to 35.16 °Brix. It was shown that temperature is the parameter that most influenced WaL%, WeL%, and SG%.